Tendon evaluation with ultrashort echo time (UTE) MRI: a systematic review - Malhi, Bhavsimran Singh; Jang, Hyungseok; Malhi, Manharjot Singh; Berry, David B.; Jerban, Saeed (Frontiers in Musculoskeletal Disorders, 2024)
Tendon disease ranks among the leading reasons patients consult their general practitioners, comprising approximately one-third of musculoskeletal appointments. Magnetic resonance imaging (MRI) is regarded as the gold standard for assessing tendons. Due to their short transverse relaxation time (T2), Tendons show up as a signal void in conventional MRI scans, which employ sequences with echo times (TEs) around several milliseconds. Ultrashort echo time (UTE) sequences utilize TEs that are 100-1,000 times shorter than those used in conventional sequences. This enables the direct visualization of tendons and assessment of their relaxation times, which is the basis for quantitative MRI. A systematic review was conducted on publications after 1990 in Google Scholar and PubMed databases. The search terms "ultrashort echo time," "tendon," and "UTE" were used to identify studies related to this investigation. This review discussed the current knowledge in quantitative UTE-MRI imaging of tendons. Quantitative UTE-T1, UTE-T2*, UTE-MT, and UTE-T1ρ techniques were described, and their reported applications in the literature were summarized in this review. We also discussed the advantages and challenges of these techniques and how these quantitative biomarkers may change in response to tendon pathology.